Common and rare genetic variants of complement components in human disease. (October 2018) - Goicoechea de Jorge, Elena; López Lera, Alberto; Bayarri-Olmos, Rafael; Yebenes, Hugo; Lopez-Trascasa, Margarita; Rodríguez de Córdoba, Santiago
Highlights: Recent advances have unraveled novel and unexpected associations of complement gene variants with disease. Fascinating genotype-phenotype correlations associate particular genetic variants in single complement genes with different diseases. Functional analyses of disease-specific variants have provided valuable insights into pathogenic mechanisms. Understanding the pathological implications of the complement genetic makeup will allow an individualized assessment of disease risk. Abstract: Genetic variability in the complement system and its association with disease has been known for more than 50 years, but only during the last decade have we begun to understand how this complement genetic variability contributes to the development of diseases. A number of reports have described important genotype-phenotype correlations that associate particular diseases with genetic variants altering specific aspects of the activation and regulation of the complement system. The detailed functional characterization of some of these genetic variants provided key insights into the pathogenic mechanisms underlying these pathologies, which is facilitating the design of specific anti-complement therapies. Importantly, these analyses have sometimes revealed unknown features of the complement proteins. As a whole, these advances have delineated the functional implications of genetic variability in the complement system, which supports the implementation of a precision medicine approach based on the complement genetic makeup of the patients. Here we provide an overview of rare complement variants and common polymorphisms associated with disease and discuss what we have learned from them.